2022
DOI: 10.1007/s10067-022-06490-8
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 as a predictor of effectiveness of treatment with TNF inhibitors in axial spondyloarthritis: data from the Swiss Clinical Quality Management Registry

Abstract: Objective To explore the impact of the human leucocyte antigen (HLA)-B27 on the effectiveness of tumor necrosis factor inhibitors (TNFi) in patients with axial spondyloarthritis (axSpA). Methods A total of 1109 patients with available HLA-B27 status (831 B27+ patients and 278 B27− patients) fulfilling the Assessment of Spondyloarthritis international Society classification criteria for axSpA from the prospective Swiss Clinical Quality Management Registry i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 18 We have previously demonstrated that CRP and male sex seem to better describe the variability of treatment responses than HLA-B27 in individual patients. 24 An elevated CRP or a higher ASDAS was consistently associated with significantly better TNFi effectiveness in the analyses presented here. Indeed, CRP was shown to be the best predictor of good response in numerous prospective trials in both radiographical and non-radiographical disease and seems better than sacroiliac inflammation detected by MRI, as demonstrated in subgroup analyses.…”
Section: Discussionmentioning
confidence: 57%
“… 18 We have previously demonstrated that CRP and male sex seem to better describe the variability of treatment responses than HLA-B27 in individual patients. 24 An elevated CRP or a higher ASDAS was consistently associated with significantly better TNFi effectiveness in the analyses presented here. Indeed, CRP was shown to be the best predictor of good response in numerous prospective trials in both radiographical and non-radiographical disease and seems better than sacroiliac inflammation detected by MRI, as demonstrated in subgroup analyses.…”
Section: Discussionmentioning
confidence: 57%
“…The HLA-B27 status is considered an important predictor in the diagnosis and treatment management of axSpA, 18 while its role in LBP on non-inflammatory origin has received limited attention thus far. Recent studies showed that in the general population, HLA-B27 status influences the extent of BMO at SIJ, especially in men.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent reported associations were with polymorphisms in TNFRSF1A/1B (TNF receptor superfamily member 1A/1B) and TNF but results were often conflicting. HLA-B27, not included in this systematic literature review, has also been identified as a predictor of good response to TNF blockers ( 31 ).…”
Section: Treatmentmentioning
confidence: 99%